Application of the International Convention on the Elimination of all Forms of Racial Discrimination (Qatar v. United Arab Emirates): Request for the Indication of Provisional Measures (I.C.J.). (2nd January 2019) - Hofer, Alexandra
Abstract : On July 23, 2018, the International Court of Justice (ICJ or Court) issued its Order on Qatar's request for provisional measures in the Qatar v. United Arab Emirates (UAE) case in which Qatar claims the UAE is responsible for violating the Convention on the Elimination of All Forms of Racial Discrimination (CERD or the Convention). The Court has previously ordered provisional measures under CERD in the context of the Ukraine v. Russia case and in the Georgia v. Russia proceedings. As is already apparent in the Order and the dissenting and separate opinions, the Qatar v. UAE case raises important issues pertaining to the interpretation of racial discrimination on the basis of "national origin" under Article 1(1) CERD as well as to the reading of the procedural conditions under Article 22 CERD.